GM-005 Financial evaluation of cataract surgery in a public health hospital. (24th March 2015) - Enneffah, W; El Wartiti, M; Cheikh, A; El Mourabit, M; Lezrek, O; Rahali, Y; Daoudi, R; Bensouda, Y
Abstract : Background: With more than 1, 000 cataracts operations performed per year, our hospital is considered one of the national reference centres for this surgery. In contrast to Extracapsular Cataract Extraction (ECCE), phacoemulsification is the most used technique at our hospital (84% of cataracts operated on) and requires costly consumables contributing to the overall cost of care. Purpose: To compare the proportion of Pharmaceutical Products (PPs) costs in the amounts billed according to cataract surgery types and to patients' Medical Tariff Categories (MTC). Material and methods: To evaluate the cost of the PPs used in uncomplicated cataract surgery with lens implantation by both standard techniques, and its impact on the amount billed to patients' MTC, we studied data from 1, 073 patients operated on in 2013 (901 by phacoemulsification and 172 by ECCE). Information relating to the cost of PPs and billing packages was collected from our hospital's financial department. Results: Our study results (table 1) reveal that for phacoemulsification, the cost of PPs consumes 64% of the billing package in insured patients and 93% of the billing package in uninsured patients, in contrast to the ECCE for which the cost of PPs consumes only 20% of the billing packages in both patients' MTC. Conclusion: Phacoemulsification is the most used technique, preferred for its many advantages. However it requires costly PPs that consume the greatest share of billing packages, especially in uninsured patients. These findings require the billing of this surgical act to be re-evaluated and a revision downwards of the necessary PP acquisition prices. References and/or acknowledgements: No conflict of interest.